The decade ahead theoretical perspectives on motivation and achievement - Karabenick, Stuart A.; Urdan, Timothy C. (Advances in motivation and achievement ;, 2010)
The Decade Ahead, takes stock of the current state of knowledge in several areas of motivation research and looks forward to the most likely and promising avenues for research in the coming decade. The chapters, from a mix of both new and veteran researchers, summarize the current state of the research in a particular area of motivation and then offer informed speculation about where the research will go in the coming decade. The volume includes chapters on the intersection of motivation and emotion, the influence of motivation research on educational policy, research on implicit motives, the application of motivation research in classrooms, sociocultural approaches to motivation research, and motivation research with African American students. By providing chapters that both sum-up and look forward, this volume offers a useful roadmap for the future of motivation research in a variety of areas.